Loan to Deposit Ratio, Risiko Kredit, Net Interest Margin dan Profitabilitas Bank - Sugeng Haryanto; Eko Aristanto; Prihat Assih; Zainal Aripin; Yanuar Bachtiar (AFRE (Accounting and Financial Review), 2021)
This study aims to analyze the effect of loan to deposit ratio, credit risk on profitability and net interest margin as moderating variables. The research was conducted on the national banking industry. The research population is the banking industry that goes public on the Indonesia Stock Exchange. The sampling technique used was purposive sampling. The research period is 2017-2019 with a sample of 37 banks. The number of pairs of data analyzed was 111 data. The data analysis technique used moderated regression analysis (MRA), with Net Interest Margin as the moderating variable. The results showed that the Loan to deposit ratio had an effect on profitability in a positive direction. Credit risk has a negative effect on bank profitability. Net interest margin is able to strengthen the relationship between loan to deposit ratio and credit risk with profitability.Â Penelitian ini bertujuan untuk menganalisis pengaruh Loan to deposit ratio, risiko kredit terhadap profitabilitas dan net interest margin sebagai variable moderasi. Penelitian dilakukan pada industry perbankan nasional. Populasi penelitian adalah industri perbankan yang go public di Bursa Efek Indonesia. Teknik sampling digunakana purposive sampling. Periode penelitian tahun 2017-2019 dengan jumlah samel 37 bank. Jumlah pasang data yang dianalisis sebanyak 111 data. Teknik analisis data menggunakan moderated regression analysis (MRA), dengan Net Interest Margin sebagai variable moderating. Hasil penelitian menunjukkan Loan to deposit ratio berpengaruh terhadap profitabilitas dengan arah positif. Risiko kredit berpengaruh negative terhadap profitabilitas bank. Net interest margin mampu memperkuat hubungan antara Loan to deposit ratio dan risiko kredit dengan profitabilitasDOI: https://doi.org/10.26905/afr.v4i1.6154